Revitalization of Dompu Traditional Industry as a Pillar of Creative Economy Based on Local Culture - Ahleyani, M.; Pratama, Andre Kurniawan; Sihombing, Ranjiv A. A; Astuti, Irma Widi; Nusantara, Althaf Fikar Harik (Buletin Ekonomika Pembangunan, 2025)
This study aims to analyse the potential for revitalising traditional industries in Dompu Regency, West Nusa Tenggara, as a pillar of creative economic development based on the local culture "Ngaha Aina Ngoho", which means the spirit of working and loving the homeland. The research method uses a descriptive qualitative approach with in-depth interview techniques with traditional industry players, local artisans, traditional leaders, and local governments. Secondary data were obtained from regional policy documents, economic statistics, and cultural studies. The findings show that various traditional industries such as weaving, woven crafts, local food processing, and performing arts have high economic potential and cultural value, but are hampered by a lack of market access, limited production technology, and minimal regeneration of young artisans. This study recommends a revitalization strategy through synergy between cultural preservation, design innovation, creative entrepreneurship training, and integration of digital technology for marketing. This revitalisation not only revives the local economy but also strengthens the cultural identity of the Dompu community in the flow of globalisation. Keywords: Traditional Industry; Creative Economy; Dompu; Local Culture; Ngaha Aina Ngoho.